Covalent Graphene‐MOF Hybrids for High‐Performance Asymmetric Supercapacitors. Issue 4 (4th December 2020) - Jayaramulu, Kolleboyina; Horn, Michael; Schneemann, Andreas; Saini, Haneesh; Bakandritsos, Aristides; Ranc, Vaclav; Petr, Martin; Stavila, Vitalie; Narayana, Chandrabhas; Scheibe, Błażej; Kment, Štěpán; Otyepka, Michal; et al.
Abstract: In this work, the covalent attachment of an amine functionalized metal‐organic framework (UiO‐66‐NH2 = Zr6 O4 (OH)4 (bdc‐NH2 )6 ; bdc‐NH2 = 2‐amino‐1, 4‐benzenedicarboxylate) (UiO‐Universitetet i Oslo) to the basal‐plane of carboxylate functionalized graphene (graphene acid = GA) via amide bonds is reported. The resultant GA@UiO‐66‐NH2 hybrid displayed a large specific surface area, hierarchical pores and an interconnected conductive network. The electrochemical characterizations demonstrated that the hybrid GA@UiO‐66‐NH2 acts as an effective charge storing material with a capacitance of up to 651 F g −1, significantly higher than traditional graphene‐based materials. The results suggest that the amide linkage plays a key role in the formation of a π‐conjugated structure, which facilitates charge transfer and consequently offers good capacitance and cycling stability. Furthermore, to realize the practical feasibility, an asymmetric supercapacitor using a GA@UiO‐66‐NH2 positive electrode with Ti3 C2 T X MXene as the opposing electrode has been constructed. The cell is able to deliver a power density of up to 16 kW kg −1 and an energy density of up to 73 Wh kg −1, which are comparable to several commercial devices such as Pb‐acid and Ni/MH batteries. Under an intermediate level of loading, the device retained 88% of its initial capacitance after 10 000 cycles. Abstract : A facile method for the preparation of graphene/metal–organic framework (MOF) hybrids with an amine‐functionalized MOF and carboxylate‐functionalized graphene via amide bonds for capacitance applications is demonstrated.